Numerical investigation of a burning fuel droplet pair with different spacings and sizes. Issue 1 (2nd January 2020) - Yang, Longbin; Shao, Yazhou; Chen, Yitung; Li, Yanjun; Song, Fuyuan; Hu, Yingming; Zhang, Guolei; Zhang, Xiaobin; Xu, Runzhang
Abstract : The combustion of double fuel droplets with different initial centre spacings and different droplet radii in convective environment are studied numerically by using the VOF (volume of fluid) model. The influences of these two factors on the droplet burning rates in the process of spray combustion are studied. The combustion processes of the two droplets with different initial centre spacings (shown as d 2 - t curves) and with different droplet radii (shown as ( d / d 0 ) 2 - t curves) are constructed respectively. Then functional analysis that reflects the global characteristic of combustion curves is proposed to process the simulation results. By analysing the functional values of combustion curves of the double droplets with different droplet centre spacings and radii, some results are obtained as follows: (1) The burning rates of the front droplets are always greater than those of the back droplets in convective environment, regardless the different droplet spacings or droplet radii. (2) The functional values of the combustion curves of the front droplets decrease nonlinearly as the initial centre spacing increases with a rapid decline first and a slow decline later, while the functional values of the combustion curves of the back droplets decrease linearly as the initial centre spacing increases. (3) The functional values of droplets combustion curves increase linearly as the droplet radius increases. In this case, the different initial centre spacings do not obviously affect the trends of the droplet burning rates versus the droplet radius.